Correlation between instrumental and sensory properties of texture‐modified carrot puree - Peh, Jie Xuan; Lim, Wensheng; Tha Goh, Kelvin Kim; Dharmawan, Jorry (Journal of texture studies, 2022)
This study was undertaken to determine the correlation between instrumental and sensory evaluation on texture‐modified carrot puree. Texture‐modified foods (TMFs) are prescribed to dysphagia individuals to aid in the oral manipulation and facilitate swallowing of food. There is a lack of correlation between instrumental measurements and sensory attributes on TMF. Understanding this correlation will aid in the formulation of safe foods with desired sensory properties for dysphagia patients. Instrumental measurements of carrot purees were performed by back extrusion method using a texture analyzer and the attributes obtained were firmness, consistency, cohesiveness, and adhesiveness. Quantitative descriptive analysis with eight trained panelists was employed to characterize the texture of the carrot puree based on seven sensory attributes: firmness, viscous, adhesive (mouth), smoothness, adhesive (throat), rate of breakdown, and difficulty to swallow. Five thickeners, namely gellan gum, xanthan gum, Suberakaze, UNI‐PURE® Dys‐sperse instant thickener, and ULTRA‐SPERSE® M Starch, were evaluated against carrot puree without any thickener as control. The correlation results obtained from texture analysis and sensory evaluation were statistically significant (p < .05). The firmness attributes from instrumental and sensory results were positively correlated. The consistency parameter was positively correlated to sensory attribute viscous and negatively correlated to smoothness. The sensory attribute rate of breakdown was negatively correlated to instrumental parameter of cohesiveness. Lastly, instrumental adhesiveness was positively correlated to sensory attributes adhesive to mouth and throat, and difficulty to swallow. The correlation results showed a well‐designed instrumental technique can be used to understand the impact of thickeners on TMF for dysphagia subjects.